Attending private tuition and its relationship with students' demographic factors / Latifah Mohd.Zain - Mohd.Zain, Latifah (2010)
This study was designed to investigate the relationship between attending private tuition and demographic factors among secondary students. In addition, this study was conducted to determine the relationship between attending private tuition and students' PMR (Penilaian Menengah Rendah) grades. The general perception of students regarding private tuitions was also investigated. 378 Form Four students from two rural schools and one urban school in Terengganu participated in this study. These students sat for their PMR in 2009, and they were asked to respond to questions regarding their preparation for PMR as far as attending (or not) any private tuition is concerned. The methodology employed was quantitative in nature.The following major findings and conclusions were drawn from the study. First, attending private tuition has a significant relationship with the students' locality, parents' qualifications and incomes. Second, there is a significant relationship between students PMR grades and attending private tuition. Students attended private tuition obtained better grades than those who did not. The third conclusion was that students in general regard private tuition as a place to go to if they want to improve their grades and parents' financial state is a factor to consider when opting for private tuition.The findings suggested that attending private tuition is beneficial for students. Regardless of their background, students who attended tuition were proven to get better results in national examinations such as PMR. Thus, further research involving a larger population needs to be carried out to ascertain the consistency of the results throughout the country.